Socio-Legal Aspects Related to Violence Against Women and the Family Group: A Review from the Optic of the SDG - Garcia Rengifo, Viviana (2025)
Objective:to analyze the socio-legal aspects related to violence against women and the family group under the focus of SDGs 5 and 16 focused on gender equality, peace and justice.Theoretical Framework: Violence against women is a serious problem in many countries;Sexual aggression is one of the most common forms of violence against women.Method:It was guided by a qualitative approach with a systematic review design; The population and sample are comprised of 19 articles, which were extracted from the databases of SCOPUS, Scielo, DOAJ and others, requiring the entry of the descriptors "Violence against women, "violence" and "violence against the family group " and " Socio-legal aspects related to violence".Results and Discussion:After the review and analysis of the articles were obtained as results that the social aspects, such as the consumption of substances and the economic situation, prevailed in the studied cases; Furthermore, the level of violence reached a high level, where the prevalent types of violence were psychological and physical.Research Implications:Accordingly, it is concluded that aspects socio-legal issues related to violence against women and the family group must be recognized opportunely by the states with the purpose of working through policies, intervention plans, political strategies, etc.Originality/Value:The innovative character of this study also lies in its proposal to consider on the ground the legal response to these phenomena, as well as the social aspects that aggravate or perpetuate them, thus promoting a more complete and holistic analysis of the problem. In order to highlight the need for a timely recognition of these aspects by the States, the investigation proposes a path towards the implementation of effective public policies that address violence from a socio-legal perspective, combining prevention, intervention and legal regulation strategies.